2022
DOI: 10.7759/cureus.22526
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Consequences of the COVID-19 Pandemic Among Ontario’s Youth: A Cross-Sectional Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has had a significant impact on the mental health and wellbeing of Ontario's youth. Our study investigated the psychological impacts of COVID-19 on the pediatric population of Ontario, using a survey derived from the Revised Children's Anxiety and Depression Scale (RCADS) system to identify children who may benefit from seeking professional help. Our cross-sectional study examined the potential risk factors that contributed to worsening mental health and wellbei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis of relatives and family members with COVID-19 was also a highly cited (4) factor shaping OCD outcomes among children and adolescents. All the studies unequivocally reported a significant association between participants' adverse OCD outcomes and diagnoses of relatives and family members [4,34,36,49]. OCD was associated with participants who lost a family member due to COVID-19 [50].…”
Section: Death or Diagnosis Of Relatives And Family Members From Covi...mentioning
confidence: 99%
“…Study [45] also narrowly studied patients with DSM-5-related psychiatric complaints. Conversely, the study [4] excluded children if they had psychological or physical comorbidities before the beginning of the COVID-19 pandemic.…”
Section: Clinical Diagnosis Of Samplementioning
confidence: 99%
See 2 more Smart Citations